Integrated Surface and Subsurface Hydrological Modeling with Snowmelt and Pore Water Freeze–Thaw. Issue 1 (6th December 2018) - Schilling, Oliver S.; Park, Young‐Jin; Therrien, René; Nagare, Ranjeet M.
Abstract: For the simulation of winter hydrological processes a gap in the availability of flow models existed: one either had the choice between (1) physically‐based and fully‐integrated, but computationally very intensive, or (2) simplified and compartamentalized, but computationally less expensive, simulators. To bridge this gap, we here present the integration of a computationally efficient representation of winter hydrological processes (snowfall, snow accumulation, snowmelt, pore water freeze–thaw) in a fully‐integrated surface water‐groundwater flow model. This allows the efficient simulation of catchment‐scale hydrological processes in locations significantly influenced by winter processes. Snow accumulation and snowmelt are based on the degree‐day method and pore water freeze–thaw is calculated with a vertical heat conduction approach. This representation of winter hydrological processes is integrated into the fully‐coupled surface water‐groundwater flow model HydroGeoSphere. A benchmark for pore water freeze–thaw as well as two illustrative examples are provided. Abstract : Article impact statement : Computationally efficient simulations of catchment‐scale winter hydrological processes in an integrated surface water‐groundwater flow model.